Advanced colorectal cancer subtypes (aCRCS) help select oxaliplatin‐based or irinotecan‐based therapy for colorectal cancer. Issue 4 (27th February 2021) - Takahashi, Shin; Sakamoto, Yasuhiro; Denda, Tadamichi; Takashima, Atsuo; Komatsu, Yoshito; Nakamura, Masato; Ohori, Hisatsugu; Yamaguchi, Tatsuro; Kobayashi, Yoshimitsu; Baba, Hideo; Kotake, Masanori; Amagai, Kenji; et al.
Abstract: Oxaliplatin (OX) and irinotecan (IRI) are used as key drugs for the first‐line treatment of metastatic colorectal cancer (mCRC). However, no biomarkers have been identified to decide which of the drugs is initially used. In this translational research (TR) of the TRICOLORE trial, the advanced colorectal cancer subtype (aCRCS) was analyzed as a potential biomarker for the selection of OX or IRI. We collected 335 (68.8%) formalin‐fixed, paraffin‐embedded (FFPE) primary tumor specimens from 487 patients registered in the TRICOLORE trial and performed direct sequencing and immunohistochemical staining of CRC‐related genes, comprehensive gene‐expression analysis, and genome‐wide methylation analysis. The progression‐free survival (PFS) of the IRI group was significantly better compared with the OX group in BRAF wild‐type (WT), PTEN‐positive, and aCRCS A1 patients. Among the molecular factors, aCRCS were only associated with the PFS of OX and IRI groups. The PFS of the IRI group was significantly better compared with the OX group in aCRCS A1 + B1 (hazard ratio [HR] = 0.58; 95% confidence interval [CI] = 0.41‐0.82; P = .0023). In contrast, the OX group had better PFS compared with the IRI group in aCRCS B2, although this was not statistically significant (HR = 1.66; 95% CI = 0.94‐2.96; P = .083). Nearly half of patients with mCRC (46.8%, aCRCS A1 + B1) respond well to IRI, while only about 18.5% (aCRCS B2) of patients with mCRC responded well to OX. In conclusion, the aCRCS might be a predictive factor for the clinical outcomes of OX‐based and IRI‐based therapies. Abstract : From translational research of TRICOLORE trail, the advanced colorectal cancer subtypes (aCRCS) can help to select oxaliplatin‐based or irinotecan‐based therapy for first‐line metastatic colorectal cancer treatment.